3rd April: 2nd Sunday of Easter - Grumett, David (The expository times, 2016)
The article presents a sermon given by Chancellor's Fellow in Christian Ethics and Practical Theology David Grummet from the School of Divinity at the University of Edinburgh for the Second Sunday of Easter. Topics covered include the different moments highlighting how Christian Messiah Jesus Christ saved the world from sin and death based on the Book of Acts, Jesus Christ's Resurrection, and explanations relating to Jesus Christ's crucifixion and death.